Από τη βυζαντινή στη βενετική τούρμα (Κρήτη, 13ος-14ος αι.) - ΓΑΣΠΑΡΗΣ, Χαράλαμπος (Byzantina Symmeikta, 2008)
Charalambos Gasparis From the Byzantine to Venetian turma. Crete, XIIIth -XlVth centuries Turma, a term coming from the Byzantine thematic system, is found very often in the XIIIth and XlVth century Venetian documents concerning the island of Crete. The Venetian turma in Crete was not an administrative or military term, but simply a geographical one, to indicate the exact post of fiefs and villages. Byzantine turma had already been used by the local Venetian governement during the first colonisation (1211) to define the six sexteria in the region of Chandax (today, Herakleion). As a military union, Byzantine turma with its castle is nothing less than the Venetian castellania, the basis of the Venetian military defense system in Crete. Although Venetian documents of the period helps us to locate the Byzantine turmae in Crete (we have the villages and the turma to which they belong), their role in the administrative and military system of the Byzantine Empire is still not very clear. The only thing we are certain about is that in the Xllth century Byzantine turma throughout the Empire has already become a geographical term as well as we find it a century later in Venetian Crete. Tables here presented contain all villages we know to which turma they belonged. There is a table for each turma and sexterium and another one with all villages in alphabetical order. There are also a plan for each territorio (Chania, Rethymno, Sitia) of medieval Crete with the turmae and the villages, and a plan with the borders of six sexteria in the territorio of Chandax.